Diversity and Distribution of Hymenoptera in Kerandangan Nature Tourism Park - Imami, Vines Salsa; Ilhamdi, Mohammad Liwa; Suyantri, Eni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hymenoptera is one of the insect orders that plays an important role in ecosystems, serving as pollinators, predators, and decomposers. This study was conducted in the Kerandangan Nature Tourism Park, located in Senggigi Village, Batu Layar Subdistrict, West Lombok Regency, West Nusa Tenggara Province. The aim of this study was to determine the diversity and distribution patterns of Hymenoptera. The research was carried out from November–December 2024 using a descriptive-exploratory method. Data were collected using two sampling techniques: pitfall traps and sweep nets, applied at three stations: Intensive Utilization Block, Protection Block, and Rehabilitation Block. The results showed the presence of 15 species from the order Hymenoptera, classified into two families: Apidae and Formicidae, with a total of 503 individuals. The overall diversity index (H') was 2,02. When ranked by diversity index values at each block, the highest diversity was found in the Protection Block (H' = 2,18), followed by the Intensive Utilization Block (H' = 1,74), and the lowest in the Rehabilitation Block (H' = 1,36). Overall, the distribution pattern of Hymenoptera individuals in TWA Kerandangan was generally random, with Morisita index values ranging from 0,00 to 0,43 (Id < 1).